Efeito da testosterona no desenvolvimento de Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae) - Ferrari, Ana C.; Soares, Andjara T. C.; Guimarães, Marco A.; Thyssen, Patrícia Jacqueline [UNESP] (My University, 2008)
Medico-Legal or Forensic Entomology can be defined as the application of the study of insects and other arthropods which, in association with criminalistic processes, have the the purpose of desovering useful information for an investigation. Nowadays, the insects are a reliable alternative for toxicological analysis, especially when tissues and liquids usually required for this purpose are absent, once insects store some ingested substances which can change their growth rate, being this a relevant fact in the determination of the cause and the time since death. Previous experiments in our laboratory on the testosterone effects on body decomposition suggested that this hormone could interfere in the cadaveric fauna development. With the objective of investigating testosterone influence on the Chrysomya albiceps larval development, a common species in cadaveric fauna, an experimental study was done from eggs of a laboratory maintained colony of this species. The eggs were divided in four groups of 30 and put in glass flasks with 50g of artificial diet in each of them, with testosterone being added in two of them. The larvae were weighted each 12 h during all interval of the larval growing. The studied larvae did not present any difference in the stages of development, but larvae from the experimental group had 5 times the weight of the larvae from the control group and with bigger size. This result shows a significant influence of testosterone in the growth of C. albiceps.
Effect of testosterone on the development of Chrysomya albiceps (Wiedemann) (Diptera: Calliphoridae)
Keywords: Diptera; Forensic entomology; Forensic medicine; Steroids; testosterone; arthropod larva; conference paper; controlled study; experimental study; fly; forensic medicine; larval development; nonhuman; organism colony; zoology